Sei sulla pagina 1di 40

SPM ZOOM–IN Form 4: Chapter 1 Functions

Paper 1

1.

The relation in the given graph can be represented using the following arrow diagram.

A

B

1 10 2 20 3 30 4 40
1
10
2
20
3
30
4
40

2.

3.

Based on the above arrow diagram,

(a)

(b)

the object of 40 is 3,

the type of the relation is many-to-many relation.

–4 –3 16 –2 9 2 4 3 4
–4
–3
16
–2
9
2
4
3
4

(a)

(b)

The above relation is a many-to-one relation.

The function which represents the above relation is f(x) = x 2 .

f 2 (x) = ff (x)

f (px + q) p (px + q) + q

=

=

= p 2 x + pq + q

It is given that f 2 (x) = 4x + 9 By comparison,

p 2 = 4

p = – 2 The question requires p < 0.
p = – 2
The question
requires p < 0.

pq + q

= 9

–2q + q

= 9

q

= 9

q

= –9

4. (a)

gf : x x 2 + 6x + 2

(x) = x 2 + 6x + 2

g(x + 4) = x 2 + 6x + 2

gf

Let x + 4 = u x = u 4

g(u) = (u 4) 2 + 6(u 4) + 2

=

u 2 8u + 16 + 6u 24 + 2

2 2u 6 g(x) = x 2 – 2x – 6

= u

(b) fg(4) = f [ 4 2 2(4) 6 ]

1

= f(2)

= 2 + 4

= 6

5. Let g 1 (x) = y g(y) = x

= x

3y + k

y

y

g 1 (x) =

=

x

k

3

1

=

3

x

1 k

3

3 x

k

3

It is given that g 1 (x) = mx

Hence, by comparison,

m =

3

k

5

6

1

3

5

=

6

and

k = 5

2

Paper 2

1.

(a)

hx x 3 hx x 3

f : x

f(x) =

Let f 1 (x) = y f(y) = x hy

= x

y 3 hy

= x (y 3)

hy = xy 3x 3x = xy hy 3x = y(x h)

y =

f 1 (x) =

3x

x h

3x

x h

But it is given that f 1 (x) =

x 2 Hence, by comparison, h = 2 and k = 3.

, x 2.

kx

(b) gf 1 (x) = g [ f 1 (x) ]

=

=

=

3x g x – 2 1 ( 3x ) x – 2
3x
g
x – 2
1
(
3x
)
x – 2

x 2

3x

gf 1 (x)

= 5x

x 2

 

3x

= 5x

x

2

= 15x 2 = 0 = 0

15x 2 + x 2 (3x 1)(5x + 2)

 

1

or 2

 

x

=

 

3

5

2.

(a)

Let f 1 (x) = y f(y) = x

 

y

2

 
 

= x

 

2

 

y

= x + 2

2

y

= 2(x + 2)

y

= 2x + 4

 

f 1 (x) = 2x + 4

f 1 (3) = 2(3) + 4 = 10

 

(b)

f

1 g(x) = f 1 [g(x)]

 

= f 1 (3x + k)

= 2(3x + k) + 4

= 6x + 2k + 4

 

But it is given that

f

1 g : x 6x 4

f

1 g (x) = 6x 4

Hence, by comparison, 2k + 4 = 4 2k = 8 k = –4

 

(c)

hf(x) : x 9x 3 h[f(x)] = 9x 3

h

Let

x

2

x

2

2

= 9x 3

2 = u

x

2 = u + 2

x = 2u + 4

h(u) = 9(2u + 4) 3 = 18u + 33

h : x 18x + 33

2

www.nitropdf.com

SPM Zoom-In Form 4: Chapter 2 Quadratic Equations

Paper 1

1. 12x 2 – 5x(2x – 1) = 2(3x + 2) 12x 2 – 10x 2 + 5x = 6x + 4 12x 2 – 10x 2 + 5x – 6x – 4 = 0 2x 2 x – 4 = 0

2.

x

x

x

x

=

–b b 2 – 4ac
–b
b 2 – 4ac

2a

=

(1)

– 4 = 0 2. x x x x = –b b 2 – 4ac 2

(1) 2 4(2)(4)

2(2)

1 33
1
33

4

=

= 1.6861 or –1.1861

Sum of roots = –

2

3

+

3

5

= –

19

15

2

5

The required quadratic equation is

x 2 +

Product of roots =

2

3

3

5

=

19

15

2

5

= 0

x +

+ Product of roots = – 2 3 – 3 5 = 19 15 2 5

x 2 (sum of roots)x + (product of roots) = 0

3.

15x 2 + 19x + 6 = 0 3x 2 + 4p + 2x = 0 3x 2 + 2x + 4p = 0

a = 3, b = 2, c = 4p

If a quadratic equation does not have real roots, then b 2 4ac < 0.

b 2 4ac < 0 2 2 4(3)(4p) < 0 4 48p < 0 48p < 4

p

p

>

>

4

48

1

12

4.

x 2 + 2x 1 + k(2x + k) = 0

 

x

2 + 2x 1 + 2kx + k 2 = 0

x

2 + 2x + 2kx + k 2 1= 0

x 2 + (2 + 2k)x + k 2 1 = 0

 

a = 1, b = 2 + 2k, c = k 2 1

If a quadratic equation has two real and distinct roots, then b 2 4ac > 0.

 

b 2 4ac > 0

 

(2 + 2k) 2 4(1)(k 2 1) > 0

 

4 + 8k + 4k 2 4k 2 + 4

> 0

8k + 8

> 0

8k > 8

k

> –1

5.

3(x 2 + 4) = 2mx 3x 2 + 12 = 2mx

3x 2 2mx + 12 = 0

a = 3, b = 2m, c = 12

If a quadratic equation has equal roots, then

b 2 4ac = 0.

b 2 4ac

= 0

(2m) 2 4(3)(12) = 0 4m 2 144 = 0 4m 2 = 144

m

2

m

m

= 36

= ±6

3

www.nitropdf.com

6. x 2 + 2x 8 = 0 a = 1, b = 2, c = 8

The roots are p and q.

Sum of roots =

b

a

2

p

+ q

=

1

p

+ q = 2

Product of roots =

c

a

 

8

pq =

1

pq = 8

The new roots are 2p and 2q.

Sum of new roots

= 2p + 2q

= 2(p + q)

= 2(2)

= 4

Product of new roots

= (2p)(2q)

= 4pq

= 4(8)

= 32

The quadratic equation that has the roots 2p and 2q is x 2 + 4x – 32 = 0.

7. x 2 (k + 2)x + 2k = 0 a = 1, b = (k + 2), c = 2k

If one of the roots is α, then the other root is 2α.

Sum of roots =

b

a

α + 2α

=

(k + 2)

 

1

3α

= k + 2 k + 2

α =

3

1
1

Product of roots =

c

a

2k 2α 2 = 1 α 2 = k … 2 Substituting 1 into 2
2k
2α 2 =
1
α 2 = k …
2
Substituting
1
into
2
:
k + 2
2
= k
3
(k
+ 2) 2
= k
9
(k
+ 2) 2
k 2 + 4k + 4
k 2 – 5k + 4
(k – 1)(k – 4)
= 9k
= 9k
= 0
= 0

k = 1 or 4

4

www.nitropdf.com

Paper 2

1. (2x 1)(x + 3) = 2x 3 k 2x 2 + 6x x 3 = 2x 3 k 2x 2 + 3x + k = 0

a = 2, b = 3, c = k

The roots are 2 and p.

Sum of roots =

b

a

3

2 + p

=

 

2

 

3

p

=

2

+ 2

1

p =

2

 

Product of roots =

c

a

k

 

2p =

2

1

2 =

2

k

2

k = –2

2. 2x 2 + (3 k)x + 8m = 0

a = 2, b = 3 k, c = 8m

The roots are m and 2m.

Sum of roots =

m + 2m

=

b

a

3 k

2

6m

= k 3

Product of roots =

m(2m) =

c

a

8m

2

2m 2 = 4m m 2 = 2m

1
1

m 2 2m

= 0

m(m 2)

= 0

m

= 0 or 2

m

= 0 is not accepted.

m

= 2

From 1 : When m = 2,
From
1
:
When m = 2,

6(2) = k 3

 

k

= 12 + 3

 

k

= 15

3.

(a)

2x 2 + px + q = 0

 
 

a

= 2, b = p, c = q

The roots are

3

and 2.

 

2

 

Sum of roots =

b

 

a

 

3

+ 2

=

p

 

2

2

 

1

=

p

2

2

p

= –1

 

Product of roots =

c

 

a

 

3

2 =

q

 
 

2

2

 

q

= –6

 

(b)

2x 2 x 6

= k

2x 2 x 6 k = 0

a = 2, b = 1, c = 6 k

If the quadratic equation does not have real roots, then b 2 4ac < 0.

When

(1) 2 4(2)(6 k) < 0

< 0

b 2 4ac < 0,

1 + 48 + 8k

8k < 49

k

k

49

<

8

< –6 1

8

5

www.nitropdf.com

SPM ZOOM–IN Form 4: Chapter 3 Quadratic Functions

Paper 1

1.

2.

3.

f(x)

= 2x 2 + 8x + 6

= 2(x 2 + 4x + 3)

4

2

= 2(x 2 + 4x + 2 2 – 2 2 + 3)

= 2[(x + 2) 2 – 1]

= 2(x + 2) 2 – 2

= 2

2 [ x 2 + 4x +

4

2

2 + 3 ]

a = 2, p = 2, q = –2

From f(x) = – (x – 4) 2 + h, we can state that the

coordinates of the maximum point are (4, h). But it is given that the coordinates of the maximum point are (k, 9). Hence, by comparison,

(a)

k = 4

 

(b)

h

= 9

(c)

The equation of the tangent to the curve at its maximum point is y = 9.

(a)

y

= (x + m) 2 + n

The axis of symmetry is x = –m.

But it is given that the axis of symmetry is

x

= 1.

 

m

= –1

When m = –1, y = (x – 1) 2 + n

Since the y-intercept is 3, the point is (0, 3).

3

= (0 – 1) 2 + n

 

n

= 2

(b)

When m = –1 and n = 2,

y = (x – 1) 2 + 2

Hence, the minimum point is (1, 2).

4.

(2 + p)(6 – p) < 7

12 + 4p p 2 – 7 < 0 –p 2 + 4p + 5 < 0 p 2 – 4p – 5 > 0

(p + 1)(p – 5) > 0

–1 5
–1
5
– 4 p – 5 > 0 ( p + 1)( p – 5) > 0

p

Hence, the required range of values of p is

p < –1 or p > 5.

5. 3x 2 + hx + 27 = 0

a = 3, b = h, c = 27

If a quadratic equation does not have real roots, b 2 – 4ac < 0 h 2 – 4(3) (27) < 0 h 2 – 324 < 0 (h + 18)(h – 18) < 0

–18 18
–18
18

h

Hence, the required range of values of h is –18 < h < 18.

6. g(x) = (2 – 3k)x 2 + (4 – k)x + 2

a = 2 – 3k, b = 4 – k, c = 2

If a quadratic curve intersects the x-axis at two distinct points, then b 2 – 4ac > 0 (4 – k) 2 – 4(2 – 3k)(2) > 0 16 – 8k + k 2 – 16 + 24k > 0 k 2 + 16k > 0 k(k + 16) > 0

k –16 0 Hence, the required range of values of k is
k
–16
0
Hence, the required range of values of k is

k < –16 or k > 0.

6

www.nitropdf.com

Paper 2

(a) f(x) = 2x 2 + 10x + k 1 2 5 2 = 25
(a) f(x) = 2x 2 + 10x + k
1 2 5 2 = 25
4
k
= 2 x 2 + 5x +
2
25
25
k
= 2 x 2 + 5x +
+
4
4 2
5
25 +
k
= 2 [ x +
2 –
]
2
4
2
5
= 2 x +
2 –
25 + k
2
2

(b) (i)

Minimum value = 32

= 32

25

2

+ k

k =

89

2

(ii) b 2 4ac < 0 10 2 4(2)(k) < 0 100 8k < 0 8k < 100

k >

k >

(c) Minimum point is –2

100

8

25

2

1

2

, 32 .

2. (a)

g(x) = 2x 2 + px 12 = 2(x + q) 2 4 2x 2 + px 12 = 2(x 2 + 2qx + q 2 ) 4 = 2x 2 4qx 2q 2 4

By comparison, p = 4q

1
1

and 12 = 2q 2 4 2q 2 = 8 q 2 = 4

q = ±2

From

When q = 2, p = 4(2) = 8 (Not accepted) When q = –2, p = 4(2) = 8 (Accepted) because p > 0 and q < 0)

1
1

:

7

(b) g(x) = 2x 2 + 8x 12 = 2(x 2) 2 4

The maximum point is (2, 4). When x = 0, y = 12 (0, 12) The graph of the function g(x) is as shown

below.

y O x (2, –4) –12
y
O
x
(2, –4)
–12
3. y = h – 2x… 1 y 2 + xy + 8 = 0
3.
y
= h – 2x…
1
y
2 + xy + 8 = 0 …
2
Substituting
1
into
2
:
(h – 2x) 2 + x(h – 2x) + 8 = 0

h 2 4hx + 4x 2 + hx 2x 2 + 8 = 0

2x 2 3hx + h 2 + 8 = 0

a = 2, b = 3h, c = h 2 + 8

If a straight line does not meet a curve, then b 2 4ac < 0

(3h) 2 4(2) (h 2 + 8)

< 0

9h 2 8h 2 64 < 0

h 2 – 64 (h + 8)(h – 8) < 0 < 0 h –8
h 2 – 64
(h + 8)(h – 8)
< 0
< 0
h
–8
8

Hence, the required range of values of h is –8 < h < 8.

www.nitropdf.com

SPM ZOOM–IN Form 4: Chapter 4 Simultaneous Equations

Paper 2

1. 2x – 3y = 2 x 2 – xy + y 2 = 4
1. 2x – 3y = 2
x 2 – xy + y 2 = 4
1
2
From
:
2 + 3y
x =
3
2 …
Substituting
into
:
2 + 3y
2 + 3y
2 – y
+ y 2 – 4
= 0
2
2
(2 + 3y)
y(2 + 3y)
2 –
+ y 2 – 4
= 0
4
2
(2 + 3y) 2 – 2y(2 + 3y) + 4y 2 – 16 = 0
4 + 12y + 9y 2 – 4y – 6y 2 + 4y 2 – 16
7y 2 + 8y – 12
= 0
= 0
(7y – 6)(y + 2) = 0
y =
6 or –2
7
From
:
6 2 + 3
(
6
)
7
16
When y =
, x =
=
7
2
7
2 + 3(–2)
When y = –2, x =
= –2
2
2
Hence, the points of intersection are 2
7 ,
7 6

and (–2, –2).

2. 4x + y = 2 … x 2 + x – y = 2
2. 4x + y = 2 …
x 2 + x – y = 2 …
1
2
From
1
:
y = 2 – 4x…
3
Substituting
x 2 + x – (2 – 4x)
x 2 + 5x – 4
3
into
2
,
= 2
= 0
–5 ±
5
2 – 4(1)(–4)
x
=
2(1)
–5 ±
41
=

2

= 0.70156 or –5.70156

, When x = 0.70156, From 3
,
When x = 0.70156,
From
3

y

When x = 5.70156, y

= 2 4(0.70156)

= 0.80624

= 2 4(5.70156)

= 24.80624

Hence, the solutions are

= 0.70156, y = –0.80624 or = –5.70156, y = 24.80624 (correct to five decimal places).

x

x

8

3. (a)

(b)

Since (16, m) is a point of intersection of

1

4 x 2 and y 2 + ky x 4 = 0, then

x = 16 and y = m satisfy both the equations.

Therefore,

m =

y =

1

4

(16) 2 = 2 and

m 2 + km – 16 – 4 = 0 2 2 + k(2) –
m
2 + km – 16 – 4
= 0
2
2 + k(2) – 16 – 4
= 0
2k
= 16
k
= 8
When k = 8,
1
y =
x – 2 …
1
4
y 2 + 8y – x – 4 = 0 …
2
From
1
:
4y
= x – 8
x
= 4y + 8 …
3
Substituting
3
into
2
,
y 2 + 8y – (4y + 8) – 4
= 0
y 2 + 8y – 4y – 8 – 4
y 2 + 4y – 12
= 0
= 0

(y 2)(y + 6) = 0 y = 2 or 6

From

When y = 2, x = 4(2) + 8 = 16 When y = 6, x = 4(6) + 8 = 16

Hence, the other point of intersection, other than (16, 2), is (–16, –6).

3
3

:

www.nitropdf.com

SPM ZOOM–IN Form 4: Chapter 5 Indices and Logarithms

Paper 1

1. 2 x+3 + 2 x + 16 (2 x1 )

= 2 x .2 3 + 2 x + 16

= 8(2 x ) + 2 x + 8(2 x )

= (8 + 1 + 8)( 2 x )

= 17(2 x )

2

x

2

2. 3 x + 3 – 3 x + 2

3 x (3 3 ) – 3 x (3 2 )

= 6

= 6

27(3 x ) – 9(3 x ) = 6 (27 – 9)(3 x ) = 6 18(3 x ) = 6

3

3

3

x

x

x

6

=

18

=

= 3 1

1

3

x = –1

3.

m = 3 a log 3 m = a

n log 3 n

log 3

= log 3 m + log 3 n 4 – log 3 27

= log 3 m + 4 log 3 n – log 3 3 3

= a + 4b – 3

mn 4

27

= 3 b = b

4.

5 x

lg 5 x

lg 5

lg 5

x lg 5 – 2x lg 3

x

x

= 3 2x–1

= lg 3 2x 1 = (2x – 1) lg 3 = 2x lg 3 – lg 3 = – lg 3

x(lg 5 – 2lg 3) = –lg 3

x

x

–lg 3 lg 5 – 2 lg 3 = 1.87

=

5. log 10 (p + 3)

= 1 + log 10 p

log 10 (p + 3) – log 10 p = 1

p + 3 log 10 = 1 p p + 3 = 10 1 p
p + 3
log 10
= 1
p
p + 3
= 10 1
p
p + 3
= 10p
9p
= 3
1
p
=
3
6. log 2 y – log 8 x
log 2 x
= 1
log 2 y –
= 1
log 2 8
log 2 x
log 2 y –
= 1
log 2 8 = log 2 2 3 = 3
3
3 log 2 y – log 2 x
log 2 y 3 – log 2 x
= 3
= 3
y 3
log 2
= 3
x
y 3
= 2 3
x
y 3
= 8x
y 3
x
=
8

9

www.nitropdf.com

SPM ZOOM–IN Form 4: Chapter 6 Coordinate Geometry

Paper 1

1.

Let point A be (0, k). AB = 10

Geometry Paper 1 1. Let point A be (0, k ). AB = 10 (0 –

(0 8) 2 + (k 7) 2 = 10

64 + k 2 – 14k + 49 = 10 2

k 2 – 14k + 13 = 0

(k – 1)(k – 13) = 0 k = 1 or 13

Based on the diagram, k < 7.

k = 1

A(0, 1)

2. (a) x + 2y + 6 = 0 x + 2y = –6 x
2.
(a) x + 2y + 6 = 0
x + 2y = –6
x 2y
–6
+
=
(–6)
(–6)
–6
Intercept form:
x
y
x
+
= 1
+ y
= 1
(–6)
(–3)
a b
–3
1
(b)
m MN = –
= –
–6
2
m = – y-intercept
x-intercept
Therefore, the gradient of the perpendicular
line is 2.
Hence, the equation of the straight line which
passes through the point N and is
perpendicular to the straight line MN is
y = 2x – 3.
x
y
3.
= 1
4
3

At point P (on the x-axis), y = 0.

x

= 1 x = 4

P is point (4, 0).

4

0

3

At point Q (on the y-axis), x = 0.

0

4

Q is point (0, –3).

y

= 1 y = –3

3

Hence, the area of ∆PQR 1 4 0 2 4 = 2 0 –3 5
Hence, the area of ∆PQR
1
4
0 2
4
=
2
0 –3
5
0
1
=
|–12 – (–6 + 20)|
2
1
=
|–26|
2
1
=
2 26
= 13 units 2
4. 2y = 3x – 12
(a)

At point L (on the x-axis), y = 0 2(0) = 3x 12

x = 4

L (4, 0)

At point N (on the y-axis), x = 0.

(b)

2y = 3(0) 12

y = 6

N (0, 6)

M =

m LN =

4 + 0

2

6 0 0 4

,

0 + (6)

2

=

3

2

= (2, –3)

Gradient of perpendicular line =

2

3

Hence, the equation of the perpendicular line is y y 1 = m(x x 1 )

y (3) =

3(y + 3) = 2(x 2)

2

3

(x 2)

3y + 9 = 2x + 4

3y = –2x – 5

5. PA = PB

3 y + 9 = – 2 x + 4 3 y = –2 x –

(x 1) 2 + (y 2) 2 (x 1) 2 + (y 2) 2

2 + ( y – 2) 2 ( x – 1) 2 + ( y –

=

(x 0) 2 + (y 3) 2 = (x 0) 2 + (y 3) 2

x 2 2x + 1 + y 2 4y + 4 = x 2 + y 2 6y + 9 2x 4y + 5 = 6y + 9

10

2x + 2y 4 x + y 2

= 0 = 0

y

= x + 2

www.nitropdf.com

Paper 2

1.

(a)

At point B (x-axis), y = 0.

0 3x + 6 = 0 x = 2

y 3x + 6 = 0

B is point (2, 0).

y 3x + 6 = 0

At point C (y-axis), x = 0.

y 3(0) + 6 = 0 y = 6

C is point (0, 6).

y

m BC = 3 m AC =

= 3x 6

1

3

Let A(k, 0).

1

3

1

3

m AC =

=

= 18

0 (6) k 0 k

k = 18

A is point (–18, 0).

(b) Let D (p, q). Midpoint of BD = Midpoint of AC

2 + p

2 + p

2

2 + p 2 , 2 + p 2

,

2 + p

2

0 + q

2

q

, 2

=

18 + 0

2

= (9, 3)

0 + (6)

, 2

Equating the x-coordinates, 2 + p

2

= 9

p = 20

Equating the y-coordinates,

q

2

q = 6

= 3

D is point (–20, –6).

(c) A(18, 0), B(2, 0), C(0, 6), D(20, 6) Area of ABCD

1 –18 2 0 –20 –18 = 2 0 0 –6 –6 0 1 =
1
–18
2
0 –20
–18
=
2
0
0 –6
–6
0
1
= |–12 – (120 + 108)|
2
1
= 240
2
= 120 units 2
2. (a)
(i)
y – 3x + 6 = 0

At point P (on the y-axis), x = 0. y 3(0) + 6 = 0 y = 6 P is point (0, –6). (ii) The coordinates of point S are

4(–6) + 3(15) 4(0) + 3(7) 3 + 4 , 3 + 4 (b) Area
4(–6) + 3(15)
4(0) + 3(7)
3 + 4
, 3 + 4
(b) Area of ∆QRS = 48 units 2
1
k
7
3 k
= 48
2
0
15
3 0

= (3, 3)

15k + 21 (45 + 3k) = 96

12k 24 = 96 12k = 120 k = 10

(c) S(3, 3), Q(10, 0), T(x, y)

TS : TQ = 2 : 3

TS

TQ

=

2

3

3TS = 2TQ 9(TS) 2 = 4(TQ) 2 9[(x 3) 2 + (y 3) 2 ] = 4[(x 10) 2 + (y 0) 2 ] 9(x 2 6x + 9 + y 2 6y + 9) = 4(x 2 20x + 100 + y 2 ) 9x 2 54x + 81 + 9y 2 54y + 81 = 4x 2 80x + 400 + 4y 2 5x 2 + 26x + 5y 2 – 54y – 238 = 0

11